'A Ticklish Craft': Viewing Britain's empire from inside a birch-bark canoe in the eighteenth century. Issue 3 (3rd July 2022) - Kurt Knoerl, T.
Abstract : At the end of the French and Indian War elements of the British Empire moved quickly into the western Great Lakes and central Canada in an effort to partake in and control the lucrative fur trade. To do this both the British army and fur traders adopted a piece of Native American technology: birch-bark canoes. What may have seemed like just an expedient tool for travelling from one point to another actually had far reaching implications for all parties involved. Archival research, material culture analysis, and geographic information systems data together demonstrate that the birch-bark canoe's speed and efficiency both facilitated and frustrated fur traders and the army alike. For the army it meant a lack of control over traders looking to skirt imperial oversight. Conversely, the trader's ability to go far beyond the government's reach put them under the power of Native communities. Decisions about how much food or trade goods to pack, which waterways to take, where to trade, where to get the canoes, and how to stay alive were all influenced by the unique characteristics of this remarkable craft.